Step by Step Golgi-Cox Staining for Cryosection - Zhong, Feng; Liu, Lei; Wei, Jia-Li; Dai, Ru-Ping (Frontiers in Neuroanatomy, 2019)
Golgi staining, though invented hundreds of years ago, is still a reliable method to study the cytoarchitecture of the brain. Almost all published Golgi staining protocols and methods were used for microtome, and rarely applied in cryosection, which restricted the application of this technique. Currently, several commercial Golgi-stain kits are available for both vibratome section and cryosection, but these kits are costly, and it is still challenging for researchers to obtain significant results. In the present study, we described a protocol of Golgi-Cox Staining for Cryosection, with the modified cryosection protection solution based on the Golgi-Cox method, which makes cryosection easy to apply in the section of the Golgi-Cox impregnated tissue. Our methods provide a low-cost and simple option for Golgi staining, and it will facilitate researchers to obtain useful Golgi staining results for neuronal architecture studies.